Systematic review: Clinical outcomes of discontinuation of oral antivirals in hepatitis B-related liver cirrhosis - Yuhao Yao; Yuhao Yao; Jiaxin Zhang; Jiaxin Zhang; Xiaoke Li; Xiaoke Li; Xiaobin Zao; Xiaobin Zao; Xiaobin Zao; Xu Cao; Guang Chen; Guang Chen; et al. (Frontiers Media S.A., 2022)
BackgroundDiscontinuation of Nucleos(t)ide analogs (NAs) remains one of the most controversial topics in the management of hepatitis B-related liver cirrhosis. However, clinical outcomes after NAs discontinuation have not been studied.AimThe aim of this systematic review is to evaluate existing data on clinical outcomes of NAs withdrawal in chronic hepatitis B (CHB) patients with cirrhosis.MethodsA literature search (until May 2022) was performed in order to identify all published studies including hepatitis B-related cirrhotic patients who discontinued NAs in virological remission with off-therapy follow-up >12 months.ResultsNineteen studies with 1,287 hepatitis B-related cirrhotic patients were included. Most cirrhotic patients were compensated and achieved complete virological suppression when they stopped the antiviral therapy. The pooled proportions of virological relapse and clinical relapse after NAs discontinuation in cirrhotic patients were 55.23 (95% CI: 40.33-69.67) and 43.56% (95% CI: 26.13-61.85), respectively. HBsAg loss was observed in 56 of 500 (pooled proportion = 13.68%, 95% CI: 5.82-24.18) cirrhotic patients. And the pooled proportions of HCC development, hepatic decompensation and overall mortality were 8.76 (95% CI: 2.25-18.95), 3.63 (95% CI: 1.31-7.03), and 0.85% (95% CI: 0.35-1.57), respectively, after NAs discontinuation in cirrhotic patients.ConclusionIn hepatitis B-related compensated cirrhosis, who have achieved complete virological suppression, discontinuation of oral antivirals still carries a high relapse rate, but the incidence of adverse events is generally low and controlled during follow-up of at least 12 months. Of attention is that discontinuation of NAs can achieve a high rate of HBsAg seroclearance. This study may be helpful in the management of NAs in cirrhotic patients.Systematic review registrationhttp://www.crd.york.ac.uk/PROSPERO, identifier: CRD42020170103.